Affine projection‐like optimal control of UIPC in networked microgrids with controllable loads - Mahdi Zolfaghari; Gevork B. Gharehpetian (IET Control Theory & Applications, 2023)
Abstract The upcoming generation of power systems would be outlined as a system of systems in which many AC and DC microgrids are interconnected to exchange power in a controlled manner. In this work, a new platform for the interconnection of multiple microgrids using a unified interphase power controller (UIPC) is presented. The networked microgrids operate in an islanded mode where voltage control in DC microgrids, and voltage and frequency control in AC microgrids are demanding. Therefore, we develop a new structure for the UIPC according to a current‐controlled four‐leg power converter configuration which can satisfy voltage and frequency support at the AC side. Due to many power and voltage oscillations, UIPC control is challenging in this heterogeneous environment. Therefore, the UIPC is equipped with a new affine projection‐like optimal control (APLOC) strategy which enables the microgrids to safely exchange power when necessary. Further, each AC or DC microgrid contains a new controllable load model which is commanded by the UIPC according to the power management paradigm. Simulation results proved the sufficiency of the proposed networked microgrids model in both controlling the exchanged power among microgrids and improving power quality problems.